The concept for innovative Comprehensive Assessment of Lowland Rivers. - Joanna Kocięcka; Jerzy Mirosław Kupiec; Mateusz Hämmerling; Daniel Liberacki (PLoS ONE, 2023)
Current river assessment methods focus on evaluating a single aspect (e.g. the physical and chemical quality of the water or its hydromorphological state) and usually do not integrate various factors. The lack of an interdisciplinary method makes it difficult to correctly assess the condition of a river as a complex ecosystem significantly influenced by humans. This study aimed to develop a novel Comprehensive Assessment of Lowland Rivers (CALR) method. It is designed to integrate and evaluate all-natural and anthropopressure-related elements that influence a river. The CALR method was developed using the Analytic Hierarchy Process (AHP). The application of the AHP allowed the assessment factors to be determined and given weights to define the importance of each assessment element. As a result of AHP analyses, the following ranks were determined for the six main parts of the CALR method: hydrodynamic assessment (0.212), hydromorphological assessment (0.194), macrophyte assessment (0.192), water quality assessment (0.171), hydrological assessment (0.152) hydrotechnical structures assessment (0.081). In the comprehensive assessment of lowland rivers, each of the six elements listed above is rated on a scale of 1-5 (where 5 means very good and 1 bad) and multiplied by an appropriate weighting. After summing up the obtained results, a final value is obtained, classifying the river. CALR can be successfully applied to all lowland rivers thanks to its relatively simple methodology. The widespread use of the CALR method may facilitate the assessment process and enable the comparison of the condition of lowland rivers worldwide. The research conducted in this article is one of the first attempts to develop a comprehensive method for evaluating rivers that considers all aspects.